Penerapan Pengendalian Anggaran Biaya Operasional PT Golden Visalux - Fifyanty, Fifyanty; Hesniati, Hesniati (Dinamika Sosial : Jurnal Pengabdian Masyarakat dan Transformasi Kesejahteraan, 2025)
This Community Service Program (PkM) was carried out at PT Golden Visalux with the aim of enhancing the effectiveness of the company’s operational cost budget control. Findings from field observations and interviews revealed that the company did not yet have formal written guidelines such as a Standard Operating Procedure (SOP) and lacked a well-structured evaluation system for its budgeting process. As a result, discrepancies occurred between planned and actual expenditures, along with delays in monitoring operational costs. Through this internship project, an SOP and budget measurement standards were created and applied as reference tools for all relevant divisions involved in the budgeting cycle. The SOP implementation led to several improvements, including more accurate cost recording, better monitoring of budget variances, and increased efficiency in operational spending. In addition, the company now possesses an official document that can be utilized continuously for evaluating and refining its cost control practices. Overall, this PkM initiative offers meaningful contributions to strengthening budget management effectiveness and supporting improved financial performance at PT Golden Visalux.